Proceedings of the 11th EAI International Conference on Mobile Multimedia Communications 2018
DOI: 10.4108/eai.21-6-2018.2276632
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Improving Deep Neural Network for Activity Recognition

Abstract: Activity recognition has become a popular research branch in the field of pervasive computing in recent years. A large number of experiments can be obtained that activity sensor-based data's characteristic in activity recognition is variety, volume, and velocity. Deep learning technology, together with its various models, is one of the most effective ways of working on activity data. Nevertheless, there is no clear understanding of why it performs so well or how to make it more effective. In order to solve thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This is, however, completely insufficient, as deep models can still encode noise such as unrelevant methods [150]. Several scientists [151], [152] have demonstrated the versatility of neural networks. After the authors discover their connections with the behaviors of the simulation, salient characteristics are sent to the following models [152].…”
Section: K Deep Learning Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is, however, completely insufficient, as deep models can still encode noise such as unrelevant methods [150]. Several scientists [151], [152] have demonstrated the versatility of neural networks. After the authors discover their connections with the behaviors of the simulation, salient characteristics are sent to the following models [152].…”
Section: K Deep Learning Modelsmentioning
confidence: 99%
“…Several scientists [151], [152] have demonstrated the versatility of neural networks. After the authors discover their connections with the behaviors of the simulation, salient characteristics are sent to the following models [152]. Nutter et al [153] converted sensory data into images, allowing for more straightforward interpretability of visualization resources for sensory data.…”
Section: K Deep Learning Modelsmentioning
confidence: 99%
“…Singh et al [19] demonstrated the use of the CNN and a comparison of results, which has been performed with Long Short Term Memory (LSTM). Xue et al [20] realized the visualization of the sensor-based activity's data features extracted from the neural network and sent the features to the DNN-based fusion model, with a reported accuracy of 96.1%.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…Therefore, we conducted an experiment that applied the MSMS-DPSO to several different classification approaches. Since we selected the SVM as the chief classifier for our study, the compared methods are (a) Random Forest (30 estimators), (b) baseline CNN classifier, (c) DNN+LSTM from [1], and (d) DeepCNN [3]. Methods (c) and (d) maintained the network structure described in the original papers.…”
Section: ) Study With Msms-dpso Approach For Different Classifiersmentioning
confidence: 99%